PASCAL'S WAGER AND THE PERSISTENT VEGETATIVE STATE - Stone, Jim (Bioethics, 2007)
I've argued that a version of Pascal's Wager applies to PVS so forcefully that no one who declines continued life without considering it makes a reasoned and informed decision. Thomas Mappes objects that my argument is much more limited than I realize. Of special interest is his appeal to an emerging diagnostic category, the ‘minimally conscious state’, to argue that there is much to lose in gambling on life. I will defend the Wager. Along the way I maintain that the chance of recovery from long-term PVS is much better than represented (as is the prospect of regaining independence if one recovers consciousness), and that the 1994 Multi-Society Task Force definitions of ‘permanent’ PVS are confused in ways that make crafting advance directives dangerously difficult. Valid advance directives require informed consent, I argue; the Wager needs to be part of the process. A consequence of my argument is that withdrawing medically-delivered nutrition and hydration from PVS patients is much harder to justify.